PENGARUH KUALITAS SISTEM INFORMASI, HARGA, PROMOSI, DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pengguna Jasa Grab Pada Mahasiswa FEB Universitas Islam Malang) - Arif Luqman Hakim; Rois Arifin; M Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
AbstractThis study aims to explain the influence of the quality of information systems, prices, promotions, and services to customer satisfaction of Grab services to students of the Faculty of Economics and Business, Malang Islamic University. The population of this study were all students of the Faculty of Economics and Business in 2015-2017 Malang Islamic University. The sample was taken using purposive sampling method so that 93 respondents were met who met the requirements as samples. This study uses primary data and multiple linear regression analysis methods.The results showed that the variable quality of information, price, promotion, and service systems partially or simultaneously had a positive and significant effect on customer satisfaction of Grab services to FEB students of Malang Islamic University.  Keywords: information system quality, price, promotion, service, customer satisfaction.